Metabolic syndrome in white European men presenting for primary couple's infertility: investigation of the clinical and reproductive burden. (1st July 2016) - Ventimiglia, E.; Capogrosso, P.; Colicchia, M.; Boeri, L.; Serino, A.; Castagna, G.; Clementi, M. C.; La Croce, G.; Regina, C.; Bianchi, M.; Mirone, V.; Damiano, R.; et al.
Summary: Despite complex interactions between obesity, dyslipidemia, hyperinsulinaemia, and the reproductive axis, the impact of metabolic syndrome on human male reproductive function has not been analysed comprehensively. Complete demographic, clinical, and laboratory data from 1337 consecutive primary infertile men were analysed. Health‐significant comorbidities were scored with the Charlson Comorbidity Index (categorised 0 vs. 1 vs. 2 or higher). NCEP‐ATPIII criteria were used to define metabolic syndrome. Semen analysis values were assessed based on the 2010 World Health Organisation (WHO) reference criteria. Descriptive statistics and logistic regression models tested the association between semen parameters and clinical characteristics and metabolic syndrome. Metabolic syndrome was found in 128 (9.6%) of 1337 men. Patients with metabolic syndrome were older ( p  < 0.001) and had a greater Charlson Comorbidity Index of 1 or higher (chi‐square: 15.6; p  < 0.001) compared with those without metabolic syndrome. Metabolic syndrome patients had lower levels of total testosterone ( p  < 0.001), sex hormone‐binding globulin ( p  = 0.004), inhibin B ( p  = 0.03), and anti‐Müllerian hormone ( p  = 0.009), and they were hypogonadal at a higher rate (chi‐square: 32.0; p  < 0.001) than patients without metabolic syndrome. Conversely, the two groups did not differ significantly in further hormonal levels, semen parameters, and rate of either obstructive or non‐obstructive azoospermia. At multivariate logistic regression analysis, testicular volume (OR: 0.90; p  = 0.002) achieved independent predictor status for WHO pathological semen concentration; conversely, age, Charlson Comorbidity Index scores, metabolic syndrome, and inhibin B values did not. No parameters predicted normal sperm morphology and total progressive motility. Metabolic syndrome accounts for roughly 9% of men presenting for primary couple's infertility. Although metabolic syndrome patients have a lower general male health status, semen analysis values seem independent of the presence of metabolic syndrome.